Management of appendicitis in coronavirus disease 2019, severe acute respiratory syndrome coronavirus 2, pandemic era: decreasing incidence with increasing complicated cases? - Kesicioglu,Tugrul (2022)
SUMMARY OBJECTIVE: This study aimed to examine the impact of the coronavirus disease 2019 (COVID-19) pandemic on appendicitis and the relevant outcomes in a tertiary hospital, designated as a “pandemic institution” by the Ministry of Health, between pre-COVID-19 and post-COVID-19, i.e., between 2019 and 2020, of the identical period in terms of the annual schedule. METHODS: The data of cases with acute appendicitis, who were followed up at the Department of General Surgery, a 400-bed, tertiary care, a university-affiliated education and research hospital, providing health care to a population of approximately 450,000 people, during the novel coronavirus SARS-CoV-2, during the identical time intervals of pre-COVID-19 (March 12, 2020 to November 12, 2020) and post-COVID-19 (March 12, 2019 to November 12, 2019), were retrospectively analyzed in a detail. RESULTS: Of the 212 appendectomy operations in total, 99 (46.7%) were performed in the pre-COVID-19 and 113 (53.3%) were performed in post-COVID-19. Compared to the pre-pandemic period, patients who had undergone appendectomies in post-COVID-19 revealed significantly lower neutrophil counts and significantly greater appendix diameters (p<0.001 for both). A significantly lower (p=0.041) acute appendicitis with abundant gangrenous appendicitis and phlegmonous appendicitis (p=0.043 and p=0.032, respectively) was recognized in post-COVID-19 compared with pre-COVID-19 interval. CONCLUSION: The number of appendectomy operations decreased in the COVID-19 pandemic. Patients operated during the pandemic period had wider appendix diameter and lower neutrophil levels. The pathological diagnosis was less frequent acute appendicitis, more frequent gangrenous appendicitis, and phlegmonous appendicitis in the pandemic period.